PENGARUH ATRIBUT, SIFAT DAN WAKTU PADA SPOT IKLAN DIAPET TERHADAP MOTIVASI DAN LOYALITAS MEREK PADA PT. RADIO SURYA BOJONEGORO - Imam Suroso (RELASI : JURNAL EKONOMI, 2014)
Advertising by radio broadcast is a kind of promotion strategy to get closer brands to their customer and for reach up sale power. Advertising production on media radio have special character which is different with another media. The way to get success on promotion by media radio can be depends on loose spot’s attributes, characteristics and duration. Precise of this research is Diapet’s loose spot which broadcasted on PT. Radio Suryo Bojonegoro aim of this research are to know direct and indirect impact of loose spot’s attributes, characteristics and duration to motivation, also to know those impact to brand loyalty. This research is an explanatory research and use survey method. The population are Bojonegoro’s citizen who are Surya Radio’s listeners, listen Diapet’s loose spot and got loyal to Diapet Brand. Sample have taken by stratified proportional sample and gotten 110 sample. This research is using description analysis and Structural Equation Model (SEM) for data analysis method. Variable of this research are loose spot’s attributes, characteristics  and duration  as exogen variable, brand loyalty as endogen variable also motivation as intervening variable. Summary of this reasearch is showing that loose spot’s attribute, character and time have direct and indirect impact to brand merk.